Frankenstein in Palestine: political monstrosity, domestic fragmentation and the possibility of return. Issue 3 (3rd July 2019) - Hamdan, Mohammed
ABSTRACT: This article employs the monstrous body of Frankenstein to examine political factionalism in the Palestinian Occupied Territories; the West Bank and Gaza. In Mary Shelley's Frankenstein and its Iraqi twin Frankenstein in Baghdad written by Ahmad Saadawi in 2013, the unnamed monster carries rich cultural and political significations that communicate certain idiosyncrasies of both English and Iraqi societies. In both narratives, the monster projects the dangers of the scientific spirit of the late eighteenth-century English society and the constant post-war traumas in Iraq after the fall of Baghdad in 2003, respectively. This article claims a third political space in which the local partisan climate has contributed to the rise of fragmentation in contemporary domestic Palestinian politics. Since 2007, Palestinian political leadership gained a new meaning after Hamas's military takeover of the Gaza Strip. The different political orientations of Fatah, Hamas, and other factions have created a new political monster that I term the Palestinian Frankenstein. The article not only suggests that the Palestinian Frankenstein is a metaphorical continuity or textual extension of Shelley's and Saadawi's conceptualisations of monstrosity but also investigates other definitions of Palestinian political monstrosity which is embodied in violent sectarianism and document-based wars between many political factions.